Edwin Courtland Dinwiddie papers - Dinwiddie, Edwin Courtland, 1867-1935.
Scrapbook (circa 1892-1905) containing correspondence, tracts, pamphlets, clippings, and other papers pertaining to temperance; and indexed list (1913-1915) of resolutions in the U.S. Congress concerning prohibition.
Clergyman and reformer.
Keywords: Prohibition; Temperance; Clergy; Reformers